Розробка компонентів crm-системи з продажу автозапчастин - Кокітко, Д. І. (ХНУРЕ, 2023)
As a result of this work, an information system was created for an online auto parts store. It is designed to store, search, edit and view a variety of information about the products of this store. The relevance of creating this information system is to scale the business for this store, since the reach of customers on the Internet is much wider than offline. This information system allows the client to familiarize himself with the list of all goods in stock, learn more about the product of interest, find out the price or place an order. The use of this platform will significantly increase the client base, turnover and profit of an auto parts store